Region-specific diversification of the highly virulent serotype 1 Streptococcus pneumoniae. Issue 2 (11th August 2015) - Cornick, Jennifer E.; Chaguza, Chrispin; Harris, Simon R.; Yalcin, Feyruz; Senghore, Madikay; Kiran, Anmol M.; Govindpershad, Shanil; Ousmane, Sani; Plessis, Mignon Du; Pluschke, Gerd; Ebruke, Chinelo; McGee, Lesley; et al.
Abstract : Serotype 1 Streptococcus pneumoniae is a leading cause of invasive pneumococcal disease (IPD) worldwide, with the highest burden in developing countries. We report the whole-genome sequencing analysis of 448 serotype 1 isolates from 27 countries worldwide (including 11 in Africa). The global serotype 1 population shows a strong phylogeographic structure at the continental level, and within Africa there is further region-specific structure. Our results demonstrate that region-specific diversification within Africa has been driven by limited cross-region transfer events, genetic recombination and antimicrobial selective pressure. Clonal replacement of the dominant serotype 1 clones circulating within regions is uncommon; however, here we report on the accessory gene content that has contributed to a rare clonal replacement event of ST3081 with ST618 as the dominant cause of IPD in the Gambia.